The bivalve Glycymeris planicostalis as a high-resolution paleoclimate archive for the Rupelian (Early Oligocene) of central Europe - E. O. Walliser; B. R. Schöne; T. Tütken; J. Zirkel; K. I. Grimm; J. Pross (Climate of the Past, 2015)
Current global warming is likely to result in a unipolar glaciated world with unpredictable repercussions on atmospheric and oceanic circulation patterns. These changes are expected to affect seasonal extremes and the year-to-year variability of seasonality. To better constrain the mode and tempo of the anticipated changes, climatologists require ultra-high-resolution proxy data of time intervals in the past, e.g., the Oligocene, during which boundary conditions were similar to those predicted for the near future. In the present paper, we assess whether such information can be obtained from shells of the long-lived bivalve mollusk Glycymeris planicostalis from the late Rupelian of the Mainz Basin, Germany. Our results indicate that the studied shells are pristinely preserved and provide an excellent archive for reconstructing changes of sea surface temperature on seasonal to interannual timescales. Shells of G. planicostalis grew uninterruptedly during winter and summer and therefore recorded the full seasonal temperature amplitude that prevailed in the Mainz Basin ~ 30 Ma. Absolute sea surface temperature data were reconstructed from δ 18 O shell values assuming a δ 18 O water signature that was extrapolated from coeval sirenian tooth enamel. Reconstructed values range between 12.3 and 22.0 °C and agree well with previous estimates based on planktonic foraminifera and shark teeth. However, temperatures during seasonal extremes vary greatly on interannual timescales. Mathematically re-sampled (i.e., corrected for uneven number of samples per annual increment) winter and summer temperatures averaged over 40 annual increments of three specimens equal 13.6 ± 0.8 and 17.3 ± 1.2 °C, respectively. Such high-resolution paleoclimate information can be highly relevant for numerical climate studies aiming to predict possible future climates in a unipolar glaciated or, ultimately, polar-ice-free world.